1999
DOI: 10.2307/3434565
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Environmental Tobacco Smoke More Strongly Associated with Coronary Heart Disease Than Expected? A Review of Potential Biases and Experimental Data

Abstract: Despite exposure levels estimated to be equivalent to smoking only 0.1-1.0 cigarettes per day, exposure to environmental tobacco smoke (ETS) is estimated to increase the risk of death from coronary heart disease (CHD) between 25 and 35% above the risk of nonexposed persons. This surprisingly large risk associated with a seemingly small exposure has raised doubts about the validity of attributing the increased CHD risk to ETS exposure. This paper reviews various biases that have been hypothesized to account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
1
25
0
4
Order By: Relevance
“…[5][6][7][8][9][10][25][26][27] Our study provides further evidence that ETS exposure is associated with cardiac autonomic dysregulation, which may be an intermediate step in the pathway to cardiac instability. 4,28 Our observations are in agreement with the findings of Pope, who described a short-term decrease in all HRV domains after acute exposure to ETS, but with relatively high standard errors in HF.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[5][6][7][8][9][10][25][26][27] Our study provides further evidence that ETS exposure is associated with cardiac autonomic dysregulation, which may be an intermediate step in the pathway to cardiac instability. 4,28 Our observations are in agreement with the findings of Pope, who described a short-term decrease in all HRV domains after acute exposure to ETS, but with relatively high standard errors in HF.…”
Section: Discussionmentioning
confidence: 68%
“…[5][6][7][8][9][10] HRV, a widely used measure of cardiac autonomic control, 11 reflects autonomic modulation of the rhythmic activity of the sinus node. 11 To date, little has been reported on the association between ETS exposure and HRV, heart rate, or blood pressure, the alterations of which may be steps in the pathophysiological pathway leading from ETS exposure to cardiopulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of an apparent dose-response relationship between the level of exposure and risk may in part be explained by physiological studies suggesting that there is a tobacco smoke exposure "threshold" rather than a linear dose-effect relationship. 140 Smoking likely contributes to increased stroke risk through both acute effects on the risk of thrombus generation in atherosclerotic arteries and chronic effects related to increased atherosclerosis. 141 Smoking just 1 cigarette increases heart rate, mean BP, and cardiac index and decreases arterial distensibility.…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Tobacco smoking has a pressing effect on the vessels, resulting in the development of arterial hypertension. Results of meta-analyses performed by several independent research centres have revealed a connection between passive smoking and CVD [20][21][22][23][24][25]. Low level of physical activity was the next problem in the population examined in our study; 46% of the participants (42% men and 54% women) did not practise any kind of physical activity during leisure time.…”
Section: Psychological Factorsmentioning
confidence: 91%